2004
DOI: 10.1111/j.1365-2265.2004.02110.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in hyperthyroidism

Abstract: Overt symptomatic hyperthyroidism is associated with decreased BMD during the first 3 years after diagnosis and treatment of the disease. After this interval, former hyperthyroid women have a Z-score near zero and not different from women without a history of the disease, apparently because of recovery of the bone density lost early during the course of the disease. Symptomatic hyperthyroidism does not seem to be a cause of long-lasting osteoporosis, and the age of the patient during the first episode is irrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 16 publications
(51 reference statements)
4
28
0
2
Order By: Relevance
“…Several studies have shown that hyperthyroidism results in bone resorption (1,2), whereas successful treatment of the disorder improves bone mineral density (BMD) (2,3). Moreover, subclinical hyperthyroidism, i.e., suppression of thyroid-stimulating hormone (TSH) without an elevation in thyroid hormones, has also been associated with bone loss (2).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that hyperthyroidism results in bone resorption (1,2), whereas successful treatment of the disorder improves bone mineral density (BMD) (2,3). Moreover, subclinical hyperthyroidism, i.e., suppression of thyroid-stimulating hormone (TSH) without an elevation in thyroid hormones, has also been associated with bone loss (2).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthyroidism in adulthood, on the other hand, is associated with increased bone turnover and a reduction in BMD at various skeletal sites due to increased cortical porosity and accelerated bone loss (7)(8)(9)(10)(11). Interestingly, population studies have shown that both hypo-and hyper-thyroidism in adults may be associated with an increased fracture risk (12).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones exert a major effect on bone metabolism by accelerating bone turnover and bone loss [5,6]. L-T4 therapy may also be accompanied by iatrogenic latent or even overt hyperthyroidism.…”
mentioning
confidence: 99%